Domestic Injuries and Physical Agents: A Disregarded Health Issue among Housewives in Raipur, India - Jaita Mondal Ghosh; Tapati Bhattacharjee (Occupational Health and Safety Society of Nepal, 2021)
Introduction: Housewives perform various household works both inside and outside the home, which may cause domestic injuries and ill health. Domestic injuries are usually sustained due to exposure to various physical agents. The objectives of the current study were to find out the various physical agents, the prevalence of various types of domestic injuries & to find out the association between domestic injuries and selected physical agents. Methods: In this study 500 housewives aged more than 18 years from villages of Raipur, Chhattisgarh were selected by multistage stratified random sampling. Demographic information, the occurrence of domestic injuries, and the factors associated with injuries were collected by questionnaires, interviews, and observation technique. Collected data were analyzed by using SPSS 16 statistical package. Results: Results showed that the mean age of housewives was 39.27 (±12.07) years and the majority of them were between 22-35 years of age group. Data revealed that 59% of housewives had suffered from domestic injuries. Out of them, the majority were suffering from vision problems (45.1%) and headache (36%), 21% suffered from heat, 15% got cut and 14.8% had fire burn from home environment. Around 14% got eye irritation and 12.8% of housewives had experienced falls on the floor. A significant association was found between injuries and physical agents. Conclusion: The study concluded that housewives are exposed to various physical agents in their own homes, which contributes to the prevalence of various types of domestic injuries among them. Housewives themselves and family members have to be aware of those physical agents present in their home which silently affecting their health.